ANALISIS TINGKAT RISIKO DENGAN KELUHAN MUSCULOSKELETAL DISORDERS (MSDS) PADA PEGAWAI PENGGUNA KOMPUTER DI POLITEKNIK ‘AISYIYAH SUMATERA BARAT TAHUN 2021 - Meta Rikandi; Trisna Jayati; Fluorina Oryza Muslim; Millani Amastasia; Rahmi Sarifatunnisa; Lindawati Lindawati; Milya Novera (Ensiklopedia of Journal, 2023)
Musculoskeletal disorders (MSDS) is a bunch of pathological condition that affects the normal functioning of the delicate tissues a musculoskeletal system that includes the nervous system, a tendon, the muscles and supporting structure like discus intervertebral. musculoskeletal disorders may include inflammation and a degenerative disease that causes weakening. bodily functionsA complaint MSDS is health problems that happen to a job that often use the power of muscles and work attitude that too many bent with the duration of the old. Hence researchers interested in looking at a deeper level analysis with complaints about the risk of a musculoskeletal disorders to a mere computer user at the polytechnic aisyiyah west sumatra years 2021.This study using the approach of cross sectional study with a method of analytic. surveyBy using rapid entire body assessment In their work and nordic body map in musculoskeletal complaints. Polytechnic aisyiyah survey areas in west sumatra in june  december 2021 .A total of 33 respondents in research is .Statistical tests used at the chi squarerank with p = 0,05 .The research suggests that work attitude = 0,037 ) ( p , the work ( p = 0,027 ) and length of employment ( p = 0,010 ) musculoskeletal significantly associated with complaints .Advice for workers always aspect ergonomics a seated position in working and long sits at while working to prevent and alleviating gripes muculoskeletal subjective.